Importance of Ozonation and Oxidation-Reduction Methods in Wastewater Treatment - Sh.J.Shakarov; I.Sh.Ergashev; M.N.Nomirov; D.T.Isakova (Genius Journals, 2023)
In the process of oxidation, the toxic impurities in the water turn into non-toxic substances as a result of a chemical reaction, so they can be separated from the water. When wastewater is treated with oxidizers, a large amount of reagent is consumed. Therefore, this method is used when it is not possible to treat wastewater pollutants by other means. Oxidation with ozone makes it possible to simultaneously discolor water, remove various tastes and odors, and neutralizes water. Ozonation of wastewater can remove phenol, petroleum products, hydrogen sulfide, arsenic compounds, surfactants, cyanides, dyes, carcinogenic aromatic hydrocarbons, and pesticides.
Keywords: Effluent; waste; ozonation; cyanides